2019
DOI: 10.1016/j.heliyon.2019.e02794
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antibacterial study of Ag–Au Bi-metallic nanocomposite by bioreduction using piper betle leaf extract

Abstract: Biological reduction method using plant extract for the synthesis of metal and metal oxides are attracted much to the researchers due to its simplicity, which integrates the chemical technology. The special attention is given to the green synthesis of nanoparticles by easily available plants with eco-friendly system compared to other conventional methods. Silver-gold nanocomposite (Ag–Au NCp's) is synthesized by biological reduction of silver nitrate and gold chloride with biological reduction method. These me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Literature showed that different labs synthesized spherical AuNPs of various sizes (5-200 nm) using leaf extract of Zingiber officinale (31), Hibiscus rosa sinensis (32), aqueous seed extract of Abelmoschus esculentus (33), buds of Syzygium aromaticum (34) etc. Similarly, BMNPs were phytofabricated in size range of 5-150 nm using different plants such as leaf extract of Piper betel (35), Plumbago zeylanica (36), Gloriosa superba (37), Antigonon leptopus (38), Chinese wolfberry fruit extract (39) and many other plants (8,40). Aqueous leaf extract of Triticum aestivum L. contains various phytochemicals which have high potential to reduce silver and gold ions into their respective NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Literature showed that different labs synthesized spherical AuNPs of various sizes (5-200 nm) using leaf extract of Zingiber officinale (31), Hibiscus rosa sinensis (32), aqueous seed extract of Abelmoschus esculentus (33), buds of Syzygium aromaticum (34) etc. Similarly, BMNPs were phytofabricated in size range of 5-150 nm using different plants such as leaf extract of Piper betel (35), Plumbago zeylanica (36), Gloriosa superba (37), Antigonon leptopus (38), Chinese wolfberry fruit extract (39) and many other plants (8,40). Aqueous leaf extract of Triticum aestivum L. contains various phytochemicals which have high potential to reduce silver and gold ions into their respective NPs.…”
Section: Discussionmentioning
confidence: 99%
“…The need for environmentally friendly synthetic procedures for nanoparticles leads to a high demand for green nanotechnology [38][39][40][41][42][43]. Many parts of plants such as leaf, fruit, stem, bark, root, leaf, and bud have been utilized for the green synthesis of Ag nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…subtilis . 228 Green synthesized CaO calcium oxide nanoparticles from betel leaf extract, which are also able to inhibit E . coli , P .…”
Section: Nanoformulationsmentioning
confidence: 99%